2018
DOI: 10.1039/c8ra05372c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent polycatecholamine nanostructures as a versatile probe for multiphase systems

Abstract: Shape and size controlled nanostructures are critical for nanotechnology and have versatile applications in understanding interfacial phenomena of various multi-phase systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…More importantly, the difference in the concentration of Zn 2+ in vivo may lead to different diseases. When Zn 2+ is excessive in the human body, it interferes with the absorption of other metal ions, which may cause metabolic disorders, diabetes, cerebral ischemia, Alzheimer's disease, and other serious diseases [5][6][7]. Besides, the lack of Zn 2+ can cause immune diseases such as diarrhea and abnormal brain Nanotechnology Nanotechnology 33 (2022) 185502 (9pp) https://doi.org/10.1088/1361-6528/ac4dc1…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the difference in the concentration of Zn 2+ in vivo may lead to different diseases. When Zn 2+ is excessive in the human body, it interferes with the absorption of other metal ions, which may cause metabolic disorders, diabetes, cerebral ischemia, Alzheimer's disease, and other serious diseases [5][6][7]. Besides, the lack of Zn 2+ can cause immune diseases such as diarrhea and abnormal brain Nanotechnology Nanotechnology 33 (2022) 185502 (9pp) https://doi.org/10.1088/1361-6528/ac4dc1…”
Section: Introductionmentioning
confidence: 99%
“…Similar to dopamine (DA), norepinephrine (NE) and epinephrine (EP) can be polymerised spontaneously under alkaline pH conditions, and self-assembled into transformable nanostructures with colloidal stability under certain reaction conditions. 19–22 Moreover, these bioinspired polymers (PNE and PEP) have been reported to be biocompatible in both in vitro and in vivo studies. 20,23–25 Therefore, a range of studies have demonstrated the potential of PNE and PEP in various biomedical fields, including in the development of efficient nanomedicines, metal ion reduction and sensing, contrast-enhanced ultrasound imaging, and imaging-guided treatments.…”
Section: Introductionmentioning
confidence: 99%